Reading Semiotics of a Madinah: A Discourse of the Topography of Fas - Kahera, Akel Ismail (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Reading Semiotics of a Madinah: A Discourse of the Topography of Fas